Alcune precisazioni riguardo la visione alla nascita - Gatti, Maria Gabriella; Fargnoli, Francesco; Fargnoli, Domenico (Il sogno della farfalla, 2023)
As theorized by Massimo Fagioli, vision is fundamental at birth for the activation of the cerebral substance: stimulation of melanopsin and rhodopsin receptors is one of the fundamental mechanisms that allows the transition from fetal to the neonatal state. Some conditions, such as light stimulation in utero performed during surgical interventions and syndromic congenital bilateral anophthalmia, allow to investigate the complexity and plasticity of neurobiological phenomena occurring at birth in which the neuropsin and sublate play a fundamental role.